توازن القوى في منطقة شمال شرق آسيا في ظل السلاح النووي الكوري - برق اللاح دومي (جامعة محمد بوضياف المسيلة, 2018)
تعتبر منطقة شمال شرق آسيا ذات أهمية استراتيجية، اكتسبتها من موقعها الجغرافي وتاريخ العلاقات بين الدول الفاعلة فيها . هذه الدول شكلت الاستثناء ومعجزة في العلاقات الدولية، بتفوقها الاقتصادي وامتلاكها السلاح النووي، مما جعلها تتكتل في أحلاف مشكلة توازن قوى في المنطقة تقوده كل من روسيا بتحالفها مع الصين وكوريا الشمالية، والولايات المتحدة بتحالفها مع اليابان وكوريا الجنوبية. لكن كوريا الشمالية صنعت الاستثناء رغم ضعفها اقتصاديا، بنجاحها بامتلاكها للسلاح النووي بقيادة ''كيم جونغ أون''، وتهديداتها بضرب كوريا الجنوبية وحلفائها، جعل كل دول المنطقة تسعى لإيجاد حل ديبلوماسي للحفاظ على مصالحها، والخوف من قيام حرب شاملة. وذلك بجمع كل من ''كيم جونغ أون'' و''دونالدترامب'' في قمة تاريخية يحول دون توحيد الكوريتين، وفي نفس الوقت تحجيم تواجد الولايات المتحدة الأمريكية في المنطقة.بإيجاد نظام توازن قوى إقليمي متعدد الأقطاب بين جميع الفواعل، من أجل الحفاظ على الاستقرار الأمني في المنطقة دون هيمنة أي قوة على الأخرى. NortheastAsiais of strategic importance, gainedfromitsgeographical location and the history of relations betweenits active countries. These countries formed the exception and miracle in international relations, withtheireconomicsuperiority and possession of nuclearweapons, whichledthem to coalesce in the alliances of balance of power in the regionled by Russia in alliance with China and NorthKorea, and the United States in alliance withJapan and South Korea. But NorthKorea made the exception, despiteitseconomicweakness, itssuccess in possessing Kim Jong-un'snuclearweapons and itsthreats to strike South Korea and its allies, making all the countries of the regionseek a diplomatic solution to safeguardtheirinterests and fear a full-scalewar. Kim Jong-un and Donald Trumpat a historicsummitthatwouldprevent the unification of the twoKoreas and at the same time limit the US presence in the region. To create a system of multi-polar regional balance of power among all actors, in order to maintainsecuritystability in the regionwithout the domination of any power over the other.
Keywords: كوريا الشمالية.السلاح النووي..استراتيجية الصينية.روسيا